2011
DOI: 10.1063/1.3569132
|View full text |Cite
|
Sign up to set email alerts
|

Solution-growth kinetics and thermodynamics of nanoporous self-assembled molecular monolayers

Abstract: The temperature and concentration dependences of the self-assembly onto graphite from solution of a series of molecular building blocks able to form nanoporous structures are analyzed experimentally by in situ scanning tunneling microscopy. It is shown that the commonly observed coexistence of dense and nanoporous domains results from kinetic blockades rather than a thermodynamic equilibrium. The ripening can be favored by high densities of domain boundaries, which can be obtained by cooling the substrate befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

15
120
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(135 citation statements)
references
References 36 publications
15
120
0
Order By: Relevance
“…Thus, it was generally believed that self-assembly at the liquid-solid interface warrants the optimum conditions to achieve equilibrium and hence leads to formation of thermodynamically stable structures. However, there is increasing evidence that some of the two-dimensional molecular networks formed at the liquidsolid interface are in fact kinetically trapped structures and may not represent the minimum energy equilibrated state [46].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it was generally believed that self-assembly at the liquid-solid interface warrants the optimum conditions to achieve equilibrium and hence leads to formation of thermodynamically stable structures. However, there is increasing evidence that some of the two-dimensional molecular networks formed at the liquidsolid interface are in fact kinetically trapped structures and may not represent the minimum energy equilibrated state [46].…”
Section: Introductionmentioning
confidence: 99%
“…A number of experimental parameters have already been identified that control the appearance of a certain type of polymorph over another. A non-comprehensive list of these parameters includes the type of solvent [23][24][25][26][27][28][29], the concentration of molecules [30][31][32][33][34][35], the type of substrate [36][37][38][39][40][41], the temperature at which the self-assembly takes place [42][43][44][45] and the thermal history of the sample [46]. How these parameters affect the self-assembly of organic building blocks is the subject of this review, with a special focus on the liquid-solid interface.…”
Section: Introductionmentioning
confidence: 99%
“…By using hydrogen bonding [5][6][7][8] , van der Waals interactions [9][10][11][12] , metal-ligand coordination [13][14][15] or a combination thereof as a molecular 'glue', a multitude of architectures have been successfully engineered both in ultra-high vacuum conditions as well as at a liquid-solid interface. Predicting the specific outcome of network formation based on the molecular building blocks remains a challenge as various experimental factors govern the selfassembly process: solute concentration, 10,[16][17][18][19][20] temperature [21][22][23][24][25] , solvent 26,27 have all been known to influence the 2D crystal formation under ambient conditions.…”
Section: Introductionmentioning
confidence: 99%
“…5 and 6), has remained prohibitive a priori. Alternatively, model calculations have been useful for identifying key qualitative features (7)(8)(9)(10)(11), whereas some full molecular dynamics simulations of the free energy using empirical force fields have been revealing for SAMs (12)(13)(14)(15) and also for macromolecules (16), and DFT molecular dynamics approaches are appearing (17). A priori computational methods have significant advantages in that they do not require parameterization, they treat interactions both generally and accurately, and, through use of implicit solvation models, they can avoid extensive liquid structure simulations.…”
mentioning
confidence: 99%
“…Experimentally testing this hypothesis requires quantitative information (7,8,33), as has been measured, e.g., for codeposition of single SAMs containing mixed porphyrins (40) to reveal that molecules inside SAM phases are not in equilibrium with those in solution. However, only limited data are available concerning relative polymorph propensities.…”
mentioning
confidence: 99%